Analysis of Recombinant Characteristics Based on 949 PRRSV-2 Genomic Sequences Obtained from 1991 to 2021 Shows That Viral Multiplication Ability Contributes to Dominant Recombination - Xingyang Cui; Dasong Xia; Xinyi Huang; Yue Sun; Mang Shi; Jianqiang Zhang; Ganwu Li; Yongbo Yang; Haiwei Wang; Xuehui Cai; Tongqing An (Microbiology Spectrum, 2022)
ABSTRACT Porcine reproductive and respiratory syndrome (PRRS) is one of the most economically important diseases affecting the pig-raising industry. The PRRS virus (PRRSV) has high genetic diversity, partly owing to viral recombination. Some individual recombinant type 2 PRRSV (PRRSV-2) strains have been detected; however, the sequence composition characteristics of recombination hot spots and potential driving forces for recombinant PRRSV-2 are still unreported. Therefore, all available genomic sequences of PRRSV-2 (n = 949, including 29 genomes sequenced in this study) from 11 countries from 1991 to 2021 were collected and analyzed. The results revealed that the dominant major recombinant parent has been converted from lineage 3 (L3) to L1 since 2012. The recombination hot spots were located at nucleotides (nt) 7900 to 8200 (in NSP9, encoding viral RNA-dependent RNA polymerase) and nt 12500 to nt 13300 (in ORF2-ORF4, mean ORF2 to ORF4); no AU-rich characteristics were found in the recombination hot spots. Based on infectious clones of L1 and L8 PRRSV-2, recombinant PRRSVs were generated by switching complete or partial NSP9 (harboring the recombination hot spot). The results showed that recombinant PRRSVs based on the L1 backbone, but not the L8 backbone, acquired a higher replication capacity in pig primary alveolar macrophages. These findings will help to understand the reason behind the dominance of L1-based recombination in PRRSV-2 strains and provide new clues for an in-depth study of the recombination mechanism of PRRSV-2. IMPORTANCE Recombination is an important driver of the genetic shifts that are tightly linked to the evolution of RNA viruses. Viral recombination contributes substantially to the emergence of new variants, alterations in virulence, and pathogenesis. PRRSV is genetically diverse, partly because of extensive recombination. In this study, we analyzed interlineage recombination based on available genomic sequences of PRRSV-2 from 1991 to 2021. The study revealed the temporal and geographical distribution of recombinant PRRSVs and the recombination hot spot’s location and showed that artificially constructed recombinant PRRSVs (harboring a high-frequency region) had more viral genomic copies than their parental virus, indicating that dominant recombination was shaped by a tendency to benefit viral replication. This finding will enrich our understanding of PRRSV recombination and provide new clues for an in-depth study of the recombination mechanism.